The long-run anthropogenic incidence on climate change, air pollution, water scarcity, and contribution to global warming in Morocco - Hamdi El Asli; Mohamed Azeroual (Sustainable Futures)
Background: Morocco experienced direct economic losses of approximately USD147.9 million due to climate-related disasters. Climate change (CC) could cost Morocco up to 6.5% of its GDP by 2050 if current trends continue, particularly due to freshwater scarcity (FWS) and droughts. For example, floods alone account for about 0.8% of GDP annually. CC affects everyday life, with 86% of Moroccan respondents indicating its impact (more details in Introduction). Methods: By setting four different pieces of emiprical evidence, to test the annual fluctuations of the same STIRPAT determinants on, CC through CO2 emissions, Atmospheric pollution by GHGs emissions, freshwater scarcity via internal freshwater whithdrawals and the share of Morocco’s contribution to global warming (CGW), from 1965 to 2023, with the ARDL, DOLS, FMOLS and CCR cointegration approaches. Findings: Economic affluence and demographic pressure, besides trade, exert a negative disproportionate impact on the four target subjects in high, low, and relatively low proportions, respectively, whereas promoting an andvanced level of education to the Moroccan youth undermines their noxiousness, all together, on environment albeit, moderately. Consclusions: Morocco's environmental sustainability (ES) is compromised by anthropogenic processes driven by affluence, demographics, and trade openness, and requires the efficient and effective implementation of policies outlined in a climate action roadmap for all stakeholders..